2014
DOI: 10.1111/iej.12380
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐CT evaluation of C‐shaped mandibular first premolars in a Brazilian subpopulation

Abstract: In this Brazilian subpopulation, C-shaped canal configuration of the root canal system was found in 67% of extracted first mandibular premolars with radicular grooves. Vertucci's types I and V were the most prevalent anatomical variations. C-shaped cross-sections were more prevalent in the middle third, and the presence of apical deltas was the most common feature in the apical third.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
36
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 20 publications
12
36
2
5
Order By: Relevance
“…In this study, the percentage frequency of C-shaped canals was high (18.57%), but within the range of 10.7% to 29% reported in the literature (9,11,13,14,16,20,28,29). In contrast, a recent micro-CT study reported C-shaped canal configuration in 67% of the mandibular first premolars with radicular grooves from a Brazilian subpopulation (30). In this study, however, radicular grooves were not classified as herein and it is possible to infer that the selected sample was composed mostly by teeth with deeper grooves, which helps to explain this higher percentage compared to the present results.…”
Section: Discussioncontrasting
confidence: 98%
“…In this study, the percentage frequency of C-shaped canals was high (18.57%), but within the range of 10.7% to 29% reported in the literature (9,11,13,14,16,20,28,29). In contrast, a recent micro-CT study reported C-shaped canal configuration in 67% of the mandibular first premolars with radicular grooves from a Brazilian subpopulation (30). In this study, however, radicular grooves were not classified as herein and it is possible to infer that the selected sample was composed mostly by teeth with deeper grooves, which helps to explain this higher percentage compared to the present results.…”
Section: Discussioncontrasting
confidence: 98%
“…, Ordinola‐Zapata et al . ). The in vivo studies performed using CBCT usually analyse a particular group of teeth, but not all of them together (Silva et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Ordinola‐Zapata et al . ). CBCT, which has a lower resolution compared to micro‐CT, is unable to capture these very small anatomic details.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The micro‐computed tomography (micro‐CT) imaging system is currently considered the gold standard for the study of root canal anatomy as it provides reproducible and detailed information regarding the two‐ and three‐dimensional aspects of the teeth (Ordinola‐Zapata et al . , , Filpo‐Perez et al . ).…”
Section: Introductionmentioning
confidence: 99%